If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(2y + 7) = -39 Reorder the terms: -3(7 + 2y) = -39 (7 * -3 + 2y * -3) = -39 (-21 + -6y) = -39 Solving -21 + -6y = -39 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -6y = -39 + 21 Combine like terms: -21 + 21 = 0 0 + -6y = -39 + 21 -6y = -39 + 21 Combine like terms: -39 + 21 = -18 -6y = -18 Divide each side by '-6'. y = 3 Simplifying y = 3
| -42+11x=-7y | | 5.4x-8.3=14.8 | | 5X+2(x-1)=3x+4x+15 | | -2-3(4-4r)=-50 | | k/1.2=-0.07 | | .333y+11=.5y-3 | | x^2+6x+3=-6 | | 2.3(m)+m=26.4 | | 5=1.6x | | 5(3+5c)=60 | | 7b^2+32b+6=0 | | 57+x=6x+7 | | x^2+2x-101=2x-1 | | 16=c-(-12) | | -28+b=-7(b+4) | | 8k+6+5k=6 | | 8-3=n-13 | | 5d-25+2d=2d | | x+12=32-3x | | x^2+6x-32=2x | | 8-3=-13n | | 4y=24-0 | | x-4-9=0 | | 3X-7=10X+4-7X-11 | | 7(x-3)-(9x+2)=15 | | 10x-5(3x+5)=-10x | | 37-17=4(x-9) | | x^2+18x+75=-6 | | 7x=52 | | -2.1=d+(-9.3) | | 75+4v=150+1v | | 6(x-6)-10= |